Cloning and Bioinformatics Analysis of GhArfGAP in Cotton (Gossypium hirsutum) Boll Abscission Layer With Ethylene Treatment - Chen, Long; Liu, AnFeng; Guo, ZiWen; Jiang, Hui; Luo, Ling; Gao, JunShan; Li, DaHui; Ye, SiHong; Guo, Ning (Frontiers in Plant Science, 2022)
Abstract: With the continuous growth of the population, the demand for fiber is also rising sharply. As one of the main fiber plants globally, the cotton fiber yield (Gossypium hirsutum)is affected by boll abscission, which is related to the formation of the abscission layer. Therefore, we explored the formation of the abscission layer of cotton. The formation of the abscission layer of cotton boll stalk was promoted by exogenous ethylene. It was found that both the number of Golgi apparatus and the number of stacking layers increased in the dissociated cells. The GhArfGAP gene family in cotton was screened by the bioinformatics method, and the species and evolutionary relationship of the GhArfGAP gene family were analyzed. qRT-PCR showed that the expression patterns of GhArfGAP13, GhArfGAP15, GhArfGAP25, and GhArfGAP34 in cotton were spatiotemporal specific. Subcellular localization suggested that GhArfGAP25 played a role in the Golgi apparatus. The expression of GhArfGAP25 in transgenic Arabidopsis thaliana increased in the root, stem, and leaf. Finally, we found that ethylene could induce the formation of an abscission layer in cotton.GhArfGAP13, GhArfGAP15, GhArfGAP25, GhArfGAP34 might regulate the changes of Golgi apparatus in the abscission layer. Taken together, the findings provide new ideas for the study of cotton abscission formation.